2001
DOI: 10.1038/sj.ijir.3900772
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of NOS isoform changes in a post radical prostatectomy model of erectile dysfunction

Abstract: Optimal treatment of erectile dysfunction (ED) following radical prostatectomy remains a subject of much controversy and is a significant concern for prostate cancer patients requiring surgical intervention. Neural stimulation involving nitric oxide synthase (NOS) is a crucial aspect of the normal erection process. In this study NOS isoform interaction was evaluated to improve our understanding of molecular changes pertaining to erection post radical prostatectomy. Bilateral cavernous nerve (CN) resected and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 34 publications
2
44
0
2
Order By: Relevance
“…Therefore, the high expression of TGF-b1 detected in this study must be the result of permanent penile flaccidity after cavernosal neurectomy which caused a low partial oxygen pressure and hypoxia in the cavernosal sinuses of rats. Another potential factor might be a decrease in nitric oxide synthase-positive nerve fibres responsible for relaxing some minor arteries in the corpus cavernosum after denervation [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high expression of TGF-b1 detected in this study must be the result of permanent penile flaccidity after cavernosal neurectomy which caused a low partial oxygen pressure and hypoxia in the cavernosal sinuses of rats. Another potential factor might be a decrease in nitric oxide synthase-positive nerve fibres responsible for relaxing some minor arteries in the corpus cavernosum after denervation [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…20 Decreased smooth muscle tissue is accompanied by increased collagen type I and III deposition in rats after bilateral neurectomy and in men after RP. 21,22 It is possible that corporal smooth muscle apoptosis and increased collagen deposition seen in the rat nerve-crush model may also be present in human patients recovering from RP. This may be associated with the time-dependent increase in the incidence of venous leak found in patients as they recover from RP.…”
Section: Pathophysiologymentioning
confidence: 99%
“…11,25 In a rat model, User and colleagues 17 found that apoptotic cells were smooth muscle cells and not endothelial cells, with cell death noted to peak at 2 days after bilateral neurectomy, suggesting early smooth muscle cell dysfunction as a mechanism for the previously observed veno-occlusive dysfunction. 26 McVary 27 has shown that both intrinsic and extrinsic apoptotic pathways were activated in rats whose cavernous nerves were disrupted.…”
Section: Introductionmentioning
confidence: 99%